PMM "Mahaga" Stunting through the Stop Stunting Campaign and "DADDU" (There’s a Clown at the Posyandu) as well as Healthy Food Education - Herda Ariyani; Aziza Fitria; Rifiana Rifiana; Ach Lutfi Arianto; Aina Habibah; Amalia Safitri; Anisa Fitri Syahrida; Annisa Dwi Oktaviani; Fatimatul Zahra; Maulinda Nur Pramudyas Primia Setyaningrum; Muhammad Naufal Rismana; Vivi Mardiani; Wanda Syahrina (Borneo Community Development, 2024)
South Kalimantan is classified as a red zone with a still high prevalence of stunting. This serious problem also occurs in the village of Bi'ih as it is the area with the highest stunting rate in Banjar district. This community service activity aims to promote literacy on stunting prevention through a campaign to enhance understanding of balanced nutritious food menus via the Student Service Program "Mahaga" Stunting at Muhammadiyah University of Banjarmasin. The method used is Door to Door to socialize and distribute posters to each family and teenagers at school. In addition, the campaign through cheerful exercise and storytelling at the integrated health posts features a clown to strengthen literacy on preventing stunting from an early age. A workshop and an interactive Q&A session involving productive mothers in educating about healthy food. The results of the activities show a significant increase in participants' knowledge and awareness regarding balanced nutritious food and efforts in preventing stunting. The conclusion of this activity is that the local approach with "DADDU" (Ada Badut Di Posyandu or There’s a Clown at the Posyandu) and campaigns using printed poster media can be effective and engaging in enhancing community knowledge.